Exploring the Dynamics of Price Competitiveness and Tourism Openness in Enhancing Bandung City’s Local Revenue - Asterina Anggraini; Annisa Wardhani; Meisa Sofia; Nuraeni Hadiati Farhani; Diara Nazifa Rizqi Kamalia (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2026)
This study analyses the dynamics of the Price Competitiveness Indicator (PCI) and Openness Indicator (OI) in driving Bandung City's Local Own-Source Revenue (PAD) during the 2019-2023 period. A quantitative descriptive method with trend analysis was used to map the changing patterns of these three variables. The results show that PCI has a strong positive correlation with PAD, where a sharp decline in 2020 due to the COVID-19 pandemic was followed by a significant recovery through 2023. In contrast, the contribution of OI to PAD was relatively small and weak, although it showed an increasing trend post-pandemic. The study's conclusion indicates that price competitiveness is the main short-term driver of PAD, while openness is more strategic for long-term growth. The policy implication is the need for a balance between price stabilization strategies and enhancing destination openness.